ANALISIS PERFORMA PERANGKAT LUNAK ANTIVIRUS DENGAN MENGGUNAKAN METODOLOGI PENGUKURAN PERFORMANCE - Ana Kurniawati; Ardiansyah Ardiansyah (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
This research aims to observe the performance of licensed enterprise antivirus software. The company Antivirus researched is Trend Micro Worry-Free Service and Kaspersky Endpoint Security. To get the data done testing on the specified antivirus parameters using the help of tools like Rebooter, BootRacer, Teracopy, Process Explorer and IP Messenger. Testing both antivirus software did as many as 8 parameters are boot time, restart, full scan, copy-paste files and use memory capacity during a full scan or when idle. The results of the data found at random are analyzed with statistical tests using Test T and test F. Tests conducted to indicate there is no significant average score difference from the test result value of 8 antivirus parameters. The result of the T-Test statistical analysis and F-test is that both anti-virus product has the advantages and disadvantages in each of the parameters with the speed of time and memory capacity used. But when calculated as a whole, antivirus Kaspersky Endpoint Security becomes the best antivirus performance.